DC conductivity of polymer nanocomposites for different types and amount of nanofiller - Jamail, N. A. M. (2012)
Polymer nanocomposites for HV insulation have been extensively being studied in recent years because of its unique properties and ability to enhance electrical performance. Electrical conduction of polymer nanocomposites have been used as one of the tool to monitor its dielectric behaviour. This paper present the experiment result for polarization and depolarization current and conductivity value to find the patterns and trends of DC conductivity. Then this experiment result will be compared with results from previous researches studies on current and conductivity analysis with different method and samples. The analysis result shown that DC conductivity exhibits significant reduction with addition of any types of nanofiller at right amount. However right percentage of nanofiller added is not same for different type of materials. This was due to decreasing of initiation probability of short circuit treeing in the insulation. The conductivity analysis shows that addition of nanofiller into the polymer improved its insulation properties.